2006
DOI: 10.1179/016164106x98008
|View full text |Cite
|
Sign up to set email alerts
|

Early combined cranioplasty and programmable shunt in patients with skull bone defects and CSF-circulation disorders

Abstract: The early reimplantation of the patient's own skull bone combined to the employment of a programmable shunt system allowed us a dynamic adjustment of the intracranial pressure (ICP) changes. The combined treatment reduced the number of required surgical procedures, complications and unsatisfactory patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 22 publications
1
37
0
4
Order By: Relevance
“…Experimental studies reported an improvement in cerebral blood flow and metabolism [10,[26][27][28]. These concerns of late cranioplasty in patients with big cranial defects were reinforced by two additional reports [22,29]. However, these studies did not determine at what time cranioplasty is most appropriate after intracranial pressure has recovered.…”
Section: Time To Cranioplastymentioning
confidence: 95%
“…Experimental studies reported an improvement in cerebral blood flow and metabolism [10,[26][27][28]. These concerns of late cranioplasty in patients with big cranial defects were reinforced by two additional reports [22,29]. However, these studies did not determine at what time cranioplasty is most appropriate after intracranial pressure has recovered.…”
Section: Time To Cranioplastymentioning
confidence: 95%
“…Aseptic resorption of the reimplanted flap is considered a particular problem, having been described in up to 50% of patients, and although age, fragmentation, and shunt dependency have been postulated as possible risk factors, the causes remain unclear. [2][3][4][5]9,18,23,24 Another possible influence on bone flap necrosis is storage of the bone flaps. Some authors have reported a higher incidence of aseptic bone resorption with cryoconserved flaps than with bone flaps stored in abdominal subcutaneuous fat.…”
Section: Discussionmentioning
confidence: 99%
“…Häufig muss man bei Patienten mit großen Kraniektomiedefekten und gleichzeitig bestehender Störung der Liquorzirkulation im Sinne eines Hydrozephalus zunächst oder gleichzeitig ein ventrikuloperitoneales (VP)-Shuntsystem einbauen. In einem anderen Report berichteten wir über die Ergebnisse der frühen kombinierten Kranioplastik und Implantation eines programmierbaren ventrikuloperitonealen Shunts bei 60 Patienten mit großen Defekten und Liquorzirkulationsstörungen [5]. Die frü-he Kranioplastik mit Reimplantation des Eigenknochens kombiniert mit der Anlage eines ventrikuloperitonealen programmierbaren Shuntsystems erlaubte in solchen Fällen eine dynamische Anpassung an die Veränderungen des intrakraniellen Druckes und Liquorresorptionswiderstandes.…”
Section: Diskussionunclassified
“…Die frü-he Kranioplastik mit Reimplantation des Eigenknochens kombiniert mit der Anlage eines ventrikuloperitonealen programmierbaren Shuntsystems erlaubte in solchen Fällen eine dynamische Anpassung an die Veränderungen des intrakraniellen Druckes und Liquorresorptionswiderstandes. Die kombinierte Therapie hat sich als sinnvoll erwiesen, insbesondere die Zahl der notwendigen Operationen (Kranioplastik, VP-Shunt-Anlage) und Komplikationen konnte somit reduziert werden [5]. Darüber hinaus gewährleistet sie auch deutliche Vorteile bezüglich des Outcomes der Patienten.…”
Section: Diskussionunclassified